Health care during the tenth plan - Ramachandran, Prema (2003)
Prior to the advent of modern medicine, Indian systems of medicine and homoeopathy had, for centuries, catered to the health care needs of the people; these systems are widely used even today because their practitioners are acceptable both geographically and culturally and their services and drugs are affordable. - Reproduced.
Keywords: Tenth Five Year Plan; Health services - India; Health services